Change in the Gravitational Centre of the Turkish Population - Cihan Ahmet Tutluoğlu; Vedia Dökmeci (European Regional Science Association (ERSA), 2005)
The centre of gravity and tendency of the mass to concentrate around it, is an important element in Physics as well as in Statistics. When it comes to population studies, they may be used to allocate governmental posts as well as to have a good grasp of the dynamics in the country. When it is a country of high changes in population, these statistics may be exploited to see the impact of these changes and enable due alignment to meet the shifting demand. Large shifts in population have marked the history of Turkey as that of many other parts of the developping world. In this paper, the change in the weighted average and the variance of population centres has been calculated for Turkey for each census at city-level and for settlements of above 10,000 inhabitants. The same was done for the GNP. The changes in the mentioned centre of gravity were then regressed on suitable trend functions and meaningful yet different dependencies have been shown. It is worthwhile to note the tendencies to converge and to draw cycles on the data set. Since all of these calculations were accompanied by huge variance terms regarding the relatively high area and population of Turkey, clusters based on variance caps have also been proposed.
Keywords: 330